Cerebral atrophy in Parkinson’s disease with and without dementia: a comparison with Alzheimer’s disease, dementia with Lewy bodies and controls - Burton, Emma J.; McKeith, Ian G.; Burn, David J.; Williams, E. David; O’Brien, John T. (Brain (London, England : 1878), 2004)
Parkinson’s disease is a common neurodegenerative disorder primarily characterized by rigidity, tremor and bradykinesia. Cognitive impairment and neuropsychiatric symptoms are frequent in Parkinson’s disease, with a 70% cumulative incidence of dementia. The aim of this cross‐sectional study was to establish the pattern of cerebral atrophy on MRI in Parkinson’s disease patients with dementia. We used voxel‐based morphometry (VBM) to provide an unbiased means of investigating brain volume loss. Whole brain structural T1‐weighted MRI scans from Parkinson’s disease patients with dementia (PDD, n = 26), Parkinson’s disease patients without dementia (n = 31), Alzheimer’s disease patients (n = 28), patients with dementia with Lewy bodies (DLB, n = 17) and control subjects (n = 36) were acquired. Images were analysed using SPM99 and the optimized method of VBM. Reduced grey matter volume in PDD patients compared with controls was observed bilaterally in the temporal lobe, including the hippocampus and parahippocampal gyrus, and in the occipital lobe, the right frontal lobe and the left parietal lobe, as well as some subcortical regions. Parkinson’s disease patients without dementia showed reduced grey matter volume in the frontal lobe compared with control subjects. There was significant grey matter atrophy bilaterally in the occipital lobe of PDD patients compared with Parkinson’s disease patients. In addition, significant temporal lobe atrophy, including the hippocampus and parahippocampal gyrus was detected in Alzheimer’s disease relative to PDD. No significant volumetric differences were observed in PDD compared with DLB. Thus, Parkinson’s disease involves grey matter loss in frontal areas. In PDD, this extends to temporal, occipital and subcortical areas, with occipital atrophy in PDD being the only difference between the two groups. This provides important information about the pattern of cerebral atrophy in Parkinson’s disease and PDD.